Valorization of Polysaccharides From Benincasa hispida: Physicochemical, Moisturizing, and Antioxidant Skincare Properties - Wang, Qian; Yang, Xiaoyan; Zhu, Changwei; Liu, Guodong; Han, Weili; Sun, Yujun; Qian, Lisheng (Frontiers in Pharmacology, 2022)
Benincasa hispida Cogn. (B. hispida) is a popular vegetable in China, and studies have been reported on B. hispida polysaccharides (BPS) preparation. However, few studies have been reported on its physicochemical and skincare properties. In this study, we analyzed the physicochemical properties of BPS, free radical scavenging capability, moisturizing and antioxidant activities in vitro and in vivo, respectively. Our results show that BPS was an inhomogeneous acidic polysaccharide that could scavenge a variety of free radicals. Also, BPS had a good moisturizing and antioxidant capability both in vitro and in vivo. Specifically, BPS could alter some key antioxidant enzyme activities and inflammatory factor levels via activating the NRF2/HO-1 pathway, thereby preventing H2O2-induced reactive oxygen species (ROS) production and apoptosis of HDF-1 cells. Our results suggest that BPS exhibited favorable moisturizing and anti-aging properties and might be an attractive candidate for the development of anti-aging skincare products.